2019
DOI: 10.1038/s41598-019-45529-w
|View full text |Cite
|
Sign up to set email alerts
|

On the molecular and cellular effects of omeprazole to further support its effectiveness as an antigiardial drug

Abstract: Research on Giardia lamblia has accumulated large information about its molecular cell biology and infection biology. However, giardiasis is still one of the commonest parasitic diarrheal diseases affecting humans. Additionally, an alarming increase in cases refractory to conventional treatment has been reported in low prevalence settings. Consequently, efforts directed toward supporting the efficient use of alternative drugs, and the study of their molecular targets appears promising. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 51 publications
0
29
0
2
Order By: Relevance
“…The in situ inactivation of N16D HsTIM with a thiol-reactive drug such as omeprazole might be linked to the accumulation of TIM metabolites, as occurred in other cell models [26]. This is the case for DHAP, one of the substrates of TIM, which in turn can be spontaneously degraded to the toxic metabolite MGO.…”
Section: Omeprazole Induces Increasing Levels Of Mgo and Ages In E Cmentioning
confidence: 95%
See 2 more Smart Citations
“…The in situ inactivation of N16D HsTIM with a thiol-reactive drug such as omeprazole might be linked to the accumulation of TIM metabolites, as occurred in other cell models [26]. This is the case for DHAP, one of the substrates of TIM, which in turn can be spontaneously degraded to the toxic metabolite MGO.…”
Section: Omeprazole Induces Increasing Levels Of Mgo and Ages In E Cmentioning
confidence: 95%
“…Next, the supernatant was collected and stored at −70 • C for further measurement. To quantify the free MGO from bacterial cells, standard values of MGO were determined according to the method described by Gilbert and Brandt [25] with modifications [26]. Stock solutions of 20 mM 2,4-dinitrophenylhydrazine (DNPH) in HCl-ethanol (12:88) and 1 mM MGO in distilled water were prepared.…”
Section: Methylglyoxal and Age Quantification In E Coli ∆Tim-bl21-gomentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that 2mercaptobenzimidazole-derived compounds possess antiparasitic properties [18][19][20]. Interestingly, one of the compounds that has the benzimidazole ring in its structure is omeprazole, which has been studied for its antigiardial properties [12,14,17,21,22]. Furthermore, it has been observed that…”
Section: Design and Synthesis Of Analog Benzimidazoles Of Omeprazolementioning
confidence: 99%
“…Recently, it has been reported that 2-mercaptobenzimidazole-derived compounds possess antiparasitic properties [18][19][20]. Interestingly, one of the compounds that has the benzimidazole ring in its structure is omeprazole, which has been studied for its antigiardial properties [12,14,17,21,22]. Furthermore, it has been observed that omeprazole and certain analogs exhibit antigiardial activity, because these compounds act as inhibitors of the glycolytic enzyme triosephosphate isomerase (TPI) of Giardia lamblia by covalent binding of benzimidazole moiety with cysteine residues [17], suggesting that this enzyme could be proposed as a potential drug target in the antigiardial activity of these compounds [12].…”
Section: Design and Synthesis Of Analog Benzimidazoles Of Omeprazolementioning
confidence: 99%